Hubungan Peranan dari Utilitarianisme Terhadap Kinerja Karyawan di Bidang Perhotelan - Jesslyn Natania; Felicia Clarisa Wijaya; Nurul Stephanie; Davina Artemesia Thonora (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the relationship between the role of Utilitarianism on Employee Performance in the Hospitality sector. The sampling method used was "purposive sampling" to select the participant group. Data analysis was carried out using SPSS 25 software. The research results showed that there was a significant influence on the variable (X) Utilitarianism and the variable (Y) Performance. This is proven by the results of the t test calculation of 4.456, whereas in the t table it is 2.0157 at a significance level of 5%, which means that Ha is accepted. Apart from that, the regression equation Y = 13.813 + 1.539 Conclusion, from the results of the t test, there is an influence between variable Y and variable Keywords: Performance, Hospitality, Utilitarianism